Analysis of the Influence of Liquidity, Profitability, Solvency, and Company Size on Company Value - Ardhaneswari, Rena; Imronudin, Imronudin (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of liquidity, profitability, solvency, and firm size on firm value among consumer non-cyclical companies listed on the Indonesia Stock Exchange in 2024. Employing a quantitative causal-associative research design and purposive sampling, the analysis focuses on firms with complete financial disclosures and publicly available market data. The study utilizes secondary data obtained from company financial reports and the Indonesia Stock Exchange database. Liquidity is measured by the Current Ratio (CR), profitability by Return on Assets (ROA) and Return on Equity (ROE), solvency by the Debt to Equity Ratio (DER), firm size by the natural logarithm of total assets, and firm value by Tobin’s Q. Descriptive statistics, diagnostic tests, and multiple linear regression analyses were conducted. The findings indicate that liquidity has a significant negative effect on firm value, while profitability has a significant positive effect. Solvency demonstrates a negative but statistically insignificant effect, and firm size exhibits a significant negative relationship with firm value. Collectively, these four variables explain a significant but limited proportion of the variance in firm value, suggesting that additional internal and external factors may also influence corporate performance.